Clinical utility of peptide microarrays in the serodiagnosis of neglected tropical diseases in sub-Saharan Africa: protocol for a diagnostic test accuracy systematic review. Issue 7 (30th July 2021) - Vengesai, Arthur; Naicker, Thajasvarie; Kasambala, Maritha; Midzi, Herald; Mduluza-Jokonya, Tariro; Rusakaniko, Simbarashe; Mduluza, Takafira
Abstract : Introduction: Neglected tropical diseases tend to cluster in the same poor populations and, to make progress with their control, they will have to be dealt with in an integrated manner. Peptide microarrays may be a solution to these problems, where diagnosis for co-infection can be detected simultaneously using the one tool. A meta-analysis using hierarchical models will be performed to assess the diagnostic accuracy of peptide microarrays for detecting schistosomiasis ( Schistosoma mansoni and S. haematobium ), soil-transmitted helminths ( Trichuris trichiura, Ascaris lumbricoides and Necator americanus ), trachoma ( Chlamydia trachomatis ), lymphatic filariasis ( Wuchereria bancrofti ) and onchocerciasis ( Onchocerca volvulus ) in people residing in sub-Saharan Africa. Methods and analysis: A comprehensive search of the following databases will be performed: Cochrane Infectious Diseases Group Specialised Register, PubMed, EMBASE and The Web of Science. Studies comparing peptide microarrays with a reference standard from a random or consecutive series of patients will be included in the study. Two review authors will independently screen titles and abstracts for relevance, assess full-text articles for inclusion and carry out data extraction using a tailored data extraction form. The quality Assessment of Diagnostic Accuracy Studies-2 tool will be used to assess the quality of the selected studies. The bivariate model and the hierarchical summary receiver operating characteristic curve model will be performed to evaluate the diagnostic accuracy of the peptide microarrays. Meta-regression analyses will be performed to investigate heterogeneity across studies. Ethics and dissemination: There is no requirement for ethical approval because the work will be carried out using previously published data, without human beings involvement. Findings will be disseminated through peer-reviewed publication and in conference presentations. PROSPERO registration number: CRD42020175145.